A novel mixed reality system to manage phantom pain in-home: results of a pilot clinical trial - Annapureddy, Drupad; Annaswamy, Thiru M.; Raval, Gargi; Chung, Yu-Yen; Prabhakaran, Balakrishnan (Frontiers in Pain Research, 2023)
Introduction: Mirror therapy for phantom limb pain (PLP) is a well-accepted treatment method that allows participants to use a mirror to visually perceive the missing limb. Mixed reality options are now becoming increasingly available, but an in-home virtual mirror therapy option has yet to be adequately investigated. Methods: We had previously developed a mixed reality system for Managing Phantom Pain (Mr. MAPP) that registers the intact limb and mirrors it onto the amputated limb with the system’s visual field, allowing the user to engage with interactive games targeting different large lower limb movements. Feasibility and pilot outcomes of treating patients with lower extremity PLP by using Mr. MAPP at home for 1 month were evaluated in this study. Pain intensity and interference were assessed using the McGill Pain Questionnaire, Brief Pain Inventory, and a daily exercise diary. Function was assessed using the Patient Specific Functional Scale (PSFS). The clinical trial registry number for this study is NCT04529083. Results: This pilot study showed that it was feasible for patients with PLP to use Mr. MAPP at home. Among pilot clinical outcomes, statistically significant differences were noted in mean current pain intensity (1.75 [SD=0.46] to 1.125 [SD=0.35] out of 5, P=.011) and PSFS goal scores (4.28 [SD=2.27] to 6.22 [SD=2.58] out of 10, P=.006), with other outcome measures showing non-significant trends towards improvement. Discussion: This pilot study revealed that in-home use of Mr. MAPP has potential to provide pain relief and improve function in patients with lower extremity PLP and is feasible. Each scale used provided unique perspective on the functional impact of PLP. Further expanded studies and investigation, including a fully powered clinical trial, with these scales are warranted.